The Fire of the Seas: A Novel About the Bitter Discrimination in Our Society - Mercellene Petra (Institute of Research and Community Outreach - Petra Christian University, 2021)
This article aims to discuss about the topic of discrimination and elaborate it through the form of a creative novel. Three topics are explored: the reasons for discrimination, how discrimination can continue to perpetuate, and how indirect discrimination can also hurt victims. These questions are answered in the narrative story in a novel with the help of the Social Dominance theory and Becker’s theory of Economic Discrimination. Sapphire is a fire-wielding mermaid who is discriminated against because of her power over fire. She finds out that discrimination can exist because the dominant group does not want to lose their privileges, and how discrimination still runs rampant because of the propaganda spread by the king, which is supported using the legalizing myths in Social Dominance theory. Sapphire also witnesses and suffers some indirect forms of discrimination, especially about lack of interaction and wage differences.Keywords: discrimination, indirect discrimination, social dominance, economic discrimination, fantasy, merfolk